The effect evaluation of the network attack based on the fuzzy comprehensive evaluation method - Ziyan Shi; Guolin Zhao; Jianhao Liu (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
With the rapid development of network technology and the prosperity of all kinds of network application, the attacks of the Internet are very frequent. the cyberspace has become a new battlefield. The network attack became a worldwide research hot spot. The network attack evaluation caused the worldwide attention, and become the cyberspace warfare analysis basis, which provides a basis for the network attack and protection. This paper analyzes the influence the effect of cyberspace. The evaluation criteria system of network attack based on the fuzzy comprehensive evaluation method was presented to promote the study of network attack in this paper. The experiment raised in this paper can prove the method mentioned in this paper.